STRATEGI PQ4R UNTUK MENINGKATKAN KETERAMPILAN MEMBACA INTENSIF SISWA KELAS IVB SD NEGERI 121 PALEMBANG - Dewi Pratama Lestari (Jurnal Inovasi Sekolah Dasar, 2016)
This study aims to improve the reading skills of Grade VI B intensive SD Negeri 121 Palembang by using strategies PQ4R totaling 38 students. The method used in this research is a method of class action carried out in three cycles. Data collection techniques that are used in this study are engineering tests and observation. The result of intensive reading students increases every cycle. Otherwise completed when the student reaches the value ? 60 learning outcomes and learning outcomes completeness 85%. Results of the study In the first cycle of the first meeting of student learning outcomes with an average value of 45.61 and completeness of student learn-ing at 28.95%. While the second meeting of student learning outcomes with an aver-age value of 52.46 and completeness of student learning at 42.10%. At the first meet-ing of the second cycle of student learning outcomes with an average value of 63.84 and completeness of student learning at 57.89%. While the second meeting of student learning outcomes with an average value of 66.21 and completeness of student learn-ing at 63.15%. At the first meeting of the third cycle of student learning outcomes with an average value of 71.34 and completeness of student learning at 73.68%. While the second meeting of student learning outcomes with an average value of 80.34 and all tuntasan student learning by 86.84%. It shows that PQ4R strategies to improve learn-ing outcomes Indonesian students in Finding the lead through intensive reading skills. Keywords: intensive reading skills, learning PQ4R, art.  Abstrak: Penelitian ini bertujuan untuk meningkatkan keterampilan membaca intensif Siswa Kelas VIb SD Negeri 121 palembang dengan mengunakan strategi PQ4R yang berjumlah 38 siswa. Metode yang digunakan dalam penelitian ini adalah metode tindakan kelas yang dilaksanakan dalam tiga siklus. Teknik pengumpulan data yang di-gunakan pada penelitian ini adalah teknik tes dan pengamatan. Hasil membaca intensif siswa meningkat setiap siklus. Siswa dinyatakan tuntas apabila mencapai nilai hasil belajar ? 60 dan ketuntasan hasil belajar 85%. Hasil penelitian Pada siklus I pertemuan pertama hasil belajar siswa dengan nilai rata-rata 45,61 dan ketuntasan belajar siswa sebesar 28,95%. Sedangkan pertemuan kedua hasil belajar siswa dengan nilai rata-rata 52,46 dan ketuntasan belajar siswa sebesar 42,10%. Pada siklus II pertemuan pertama hasil belajar siswa dengan nilai rata-rata 63,84 dan ketuntasan belajar siswa sebesar 57,89%. Sedangkan pertemuan kedua hasil belajar siswa dengan nilai rata-rata 66,21 dan ketuntasan belajar siswa sebesar 63,15%. Pada siklus III pertemuan pertama hasil belajar siswa dengan nilai rata-rata 71,34 dan ketuntasan belajar siswa sebesar 73,68%. Sedangkan pertemuan kedua hasil belajar siswa dengan nilai rata-rata 80,34 dan ke-tuntasan belajar siswa sebesar 86,84%. Hal tersebut menunjukkan bahwa strategi PQ4R dapat meningkatkan hasil belajar bahasa Indonesia siswa dalam Menemukan kalimat utama melalui keterampilan membaca intensif. Kata kunci: keterampilan membaca intensif, PQ4R pembelajaran, seni rupa.